2019
DOI: 10.5005/jp-journals-10024-2522
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weight Reduction on Adiponectin and TNF-α Levels in the Gingival Crevicular Fluids of Obese Patients with and without Periodontal Disease

Abstract: Aim:The aim of the current study was to assess the impact of weight loss on the gingival crevicular fluids (GCF) levels of adiponectin and TNF-α in obese patients with periodontal disease. Materials and methods:Sixty obese subjects were recruited into the study and were divided into three groups of 20 each. Group 1-periodontally healthy obese patients, group 2-obese patients with gingivitis, group 3-obese patients with periodontitis. The GCF levels of adiponectin and tumor necrosis factor α (TNF-α) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These results are in concordance with previous studies that have found TNF‐α and IL‐1β to be significantly elevated in GCF of obese healthy individuals along with a greater degree of gingival inflammation 74,75 . Another study found a decrease in the GCF levels of TNF‐α with a simultaneous increase in adiponectin levels after weight reduction 60 . A systematic review reported that subjects with periodontitis had a 30% greater chance of being diagnosed with obesity and a higher BMI 36 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are in concordance with previous studies that have found TNF‐α and IL‐1β to be significantly elevated in GCF of obese healthy individuals along with a greater degree of gingival inflammation 74,75 . Another study found a decrease in the GCF levels of TNF‐α with a simultaneous increase in adiponectin levels after weight reduction 60 . A systematic review reported that subjects with periodontitis had a 30% greater chance of being diagnosed with obesity and a higher BMI 36 .…”
Section: Discussionsupporting
confidence: 91%
“…The most common reasons for exclusion were no obesity group included ( n = 34), smokers included ( n = 26), and subjects with other systemic diseases/conditions included ( n = 11) (Table S2). Seventeen articles were included in the meta‐analysis 20–23,25,51–62 . One study included groups with three grades of obesity and only one group was included since hyper‐glycemic subjects were included in other groups 63 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations